Correction: Gold-loaded nanoporous iron oxide nanocubes: a novel dispersible capture agent for tumor-associated autoantibody analysis in serum. Issue 36 (12th September 2017) - Yadav, Sharda; Masud, Mostafa Kamal; Islam, Md. Nazmul; Gopalan, Vinod; Lam, Alfred King-yin; Tanaka, Shunsuke; Nguyen, Nam-Trung; Al Hossain, Md. Shahriar; Li, Cuiling; Yamauchi, Yusuke; Shiddiky, Muhammad J. A.
Abstract : Correction for 'Gold-loaded nanoporous iron oxide nanocubes: a novel dispersible capture agent for tumor-associated autoantibody analysis in serum' by Sharda Yadav et al., Nanoscale, 2017, 9, 8805–8814.